Molecular Dynamics of Amphiphilic Random Copolymers in the Bulk: A 1H and 19F NMR Relaxometry Study. Issue 16 (12th July 2019) - Martini, Francesca; Guazzelli, Elisa; Martinelli, Elisa; Borsacchi, Silvia; Geppi, Marco; Galli, Giancarlo
Abstract: A set of amphiphilic random copolymers of poly(ethylene glycol) methacrylate (PEGMA) and perfluorohexylethyl acrylate (FA) with different compositions synthesized by atom transfer radical polymerization (ATRP) is investigated by 1 H and 19 F NMR relaxometry. In particular, a thorough investigation of T1 and T2 relaxation times at variable temperature and copolymer composition provides the first complete and detailed characterization of the dynamics of both the main chain backbone and the side chains of the PEGMA‐ co ‐FA copolymers. The results highlight an intramolecular segregation of rigid main chain and mobile side chains, and an additional self‐assembling of the PEGMA and FA side chains into distinct nanodomains, driven by the hydrophobic interactions between FA side chains. The obtainment and observation of nanoscale phase separation in random copolymers is a promising achievement to the aim of controlling self‐assembly in the bulk by suitably modulating copolymers composition, which can open novel avenues to easier fabrications and applications in nanotechnologies. Abstract : The dynamics of amphiphilic random copolymers of poly(ethylene glycol) methacrylate (PEGMA) and perfluorohexylethyl acrylate (FA) is thoroughly characterized by the analysis of 1 H and 19 F T1 and T2 relaxation times. Intramolecular segregation of rigid main chain and mobile side chains occurs, and additionally the PEGMA and FA side chains self‐assemble into distinct nanodomains.